2020
DOI: 10.1039/d0se00500b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal input/output and operation characteristics of a chemical heat pump using the hydration reaction of calcium sulphate

Abstract: The heat cycle characteristics of composited-CaSO4 hydration CHPs using heat exchanger with slits for heat upgrading are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Given its application as a binder and building material, attention has also been paid to the hydration-dehydration processes of calcium sulfate for chemical heat pumps. CaSO 4 hydration CHPs offer certain advantages, such as high heat density, using only safe and economical materials, no deliquescence, very small hysteresis, negligible expansion in hydration, long-term storage of the absorbent and products, and low heat loss (Shiren et al, 2020). As the main disadvantages, previous studies have reported the problem of inactivation of CaSO 4 due to hydration under high water vapor pressure (Lee et al, 2014;Richter et al, 2018); however, CaSO4 has the potential to 2014) studied the same reaction also for a CHP system, storing heat at around 100 °C.…”
Section: Calcium Sulfatementioning
confidence: 99%
See 1 more Smart Citation
“…Given its application as a binder and building material, attention has also been paid to the hydration-dehydration processes of calcium sulfate for chemical heat pumps. CaSO 4 hydration CHPs offer certain advantages, such as high heat density, using only safe and economical materials, no deliquescence, very small hysteresis, negligible expansion in hydration, long-term storage of the absorbent and products, and low heat loss (Shiren et al, 2020). As the main disadvantages, previous studies have reported the problem of inactivation of CaSO 4 due to hydration under high water vapor pressure (Lee et al, 2014;Richter et al, 2018); however, CaSO4 has the potential to 2014) studied the same reaction also for a CHP system, storing heat at around 100 °C.…”
Section: Calcium Sulfatementioning
confidence: 99%
“…Richter et al (2018), in their material screening study, also included calcium sulfate, which showed appropriate temperature levels for the reversible hydration reaction and a small reaction hysteresis. Recently, Shiren et al (2020) studied calcium sulfate for waste heat recovery at a temperature of 423 K or less.…”
Section: Calcium Sulfatementioning
confidence: 99%
“…Many thermal applications using CaCl 2 have been demonstrated extensively [12] [13]. This material has the outstanding features of low cost, nontoxicity, and thermochemical stability.…”
Section: Introductionmentioning
confidence: 99%